2010
DOI: 10.1093/pch/15.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Sexting: Keeping teens safe and responsible in a technologically savvy world

Abstract: The recommendations in this statement do not indicate an exclusive course of treatment or procedure to be followed.Variations, taking into account individual circumstances, may be appropriate. All Canadian Paediatric Society position statements/notes are reviewed, revised or retired as needed on a regular basis.For the most current version, please consult the "Position Statements" section of the CPS Web site (www.cps.ca/english/publications/statementsindex.htm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 2 publications
0
21
2
2
Order By: Relevance
“…Unlike work that has suggested that sexting is a lowrisk, or healthy alternative to sexual risk taking, 2,11,12 we find that there is a clustering of sexual risk behaviors, which includes sexting. Sexting was statistically significantly associated with sexual activity and showed a nearsignificant trend with reports of unsafe sex (ie, not using a condom at last intercourse).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike work that has suggested that sexting is a lowrisk, or healthy alternative to sexual risk taking, 2,11,12 we find that there is a clustering of sexual risk behaviors, which includes sexting. Sexting was statistically significantly associated with sexual activity and showed a nearsignificant trend with reports of unsafe sex (ie, not using a condom at last intercourse).…”
Section: Discussioncontrasting
confidence: 99%
“…4,11 Sexting may be another means of adolescents exploring their sexuality, engaging in sexual experimentation, identity and self-development, and determining his or her moral and sexual values. 3,11,12 Sexting itself does not pose a direct risk for transmission of STIs or unwanted pregnancy, and could, in fact, be considered a "safe" alternative to actual sexual behavior, if sexting behavior remained strictly "online" and was not associated with physical sex risk behavior. Some adolescents perceive that sexting is a safer substitute to real life sexual activity, 2 but others suggest that sexting may be viewed as a future expectation for engaging in sexual intercourse.…”
Section: Resultsmentioning
confidence: 99%
“…Before introducing the concept of sexting, teachers could describe it as the practice of exchanging sexually explicit written and visual messages by cell phone or on the Internet. This description could be used in school policy documents and prevention materials, as well as during classroom discussions (Katzman 2010). • Integrate sexting prevention into lessons about cyberbullying, health, and sex education.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Er gelangte bei der vom New Oxford American Dictionary ausgerichteten Wahl zum "Wort des Jahres 2009" sogar unter die Finalisten. "Sexting" (englisches Kofferwort aus "Sex" und "Texting") bezieht sich auf den interpersonalen Austausch von selbstproduzierten freizügigen Fotos -seltener Videos -per multimedialem Handy-Kurzmitteilungsdienst MMS (Chalfen 2009;PewResearchCenter 2009;Katzman 2010;Ferguson 2010). Dementsprechend lassen sich zwei Komponenten des Sachverhalts differenzieren: -Die Texting-Komponente des Sexting: Die große Mehrheit der Jugendlichen -in Deutschland 97 % (MPFS 2010: 7) -verfügt heute über ein Handy, und viele Modelle enthalten eine integrierte Foto-und Video-Kamera (vgl.…”
Section: Was Versteht Man Unter Sexting?unclassified
“…Medienpäda-gogische Ansätze konzentrieren sich darauf, Negativfolgen aufzuzeigen und Sexting-Abstinenz zu propagieren (vgl. Katzman 2010). Heranwachsenden pauschal nahe zu legen, niemals freizügige Handy-Bilder zu produzieren, ist jedoch ebenso nutzlos wie der Hinweis, sie sollten nichts Persönliches ins Internet stellen.…”
unclassified